Ground penetrating radar and electrical resistivity tomography investigations in the southern sector of the Roman Forum: First results on the pre‐Augustan phases of the Basilica Julia. Issue 2 (22nd November 2020) - Scardozzi, Giuseppe; Ismaelli, Tommaso; Leucci, Giovanni; De Giorgi, Lara; Ditaranto, Immacolata; Galli, Marco; Inglese, Carlo; Griffo, Marika
Abstract: A research project aimed at the study of the archaeological context of the Basilica Julia in the Roman Forum (Rome, Italy) and the transformation phases of the building involved the use of different techniques of geophysical prospecting. In particular, Ground‐penetrating Radar (GPR) and Electrical Resistivity Tomography (ERT) surveys were carried out in order to record the buried structures of the Basilica and the previous buildings laying in the southern part of the Forum. These geophysical methods have been chosen in order to guarantee a good compromise between resolution (GPR in the shallow subsurface) and depth of investigation (ERT in the deeper subsurface), with the aim of investigating up to a depth of about 10 m in a very conductive subsoil. In particular, GPR surveys were conducted in the five aisles of the monument, while ERT measurements were performed with nonstandard acquisition mode in order to include the entire perimeter of the building. These techniques allowed us to acquire new data on the structures buried in the sectors of the monumental complex that have never been excavated and on the paleosoil till a depth of about 10 m from the surface. Interesting data were acquired on the Basilica Julia itself, built during the late Republican period (54–46 BC) and rebuilt at the beginning of the first century AD, such as the technical features of the caementicium and travertine foundations, their relationship with the Cloaca Maxima and the traces of a design change occurred during the construction in the central aisle of the building; other buried remains of the previous Basilica Sempronia, constructed in 169 BC in the same area, were identified. Moreover, the investigations documented the paleosoil in the area between the Forum and the Velabrum to the south, between 7.5–8.5 and 5.5 m a.s.l. These data confirmed the general geological setting of the area, obtained from previous coring, but significantly specified the geomorphology of this border sector of the Roman Forum, which slopes down towards the south and the west.